Non gastro-esophageal reflux disease related esophagitis: an overview with a histologic diagnostic approach: Review - Mastracci, Luca; Grillo, Federica; Parente, Paola; Unti, Elettra; Battista, Serena; Spaggiari, Paola; Campora, Michela; Valle, Luca; Fassan, Matteo; Fiocca, Roberto (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
Several pathological conditions, other than gastro-esophageal reflux disease and its complications, can affect the esophagus. While some of these can present with unspecific lesions (i.e. ulcers and epithelial damage) and require clinico-pathological correlation for diagnosis (i.e. drug-induced esophagitis and corrosive esophagitis) other conditions show distinctive histological lesions which enable the pathologist to reach the diagnosis (i.e. some specific infectious esophagites and Crohn’s disease). In this context eosinophilic esophagitis is the condition which has been increasingly studied in the last two decades, while lymphocytic esophagitis, a relatively new entity, still represents an enigma. This overview will focus on and describe histologic lesions which allow pathologists to differentiate between these conditions.